A Model Demonstration Service Delivery Continuum for Preschool Handicapped Children. Final Program Performance Report, July 1, 1979-June 30, 1980 - Schennum, Ruth H.; Rhode Island Coll., Providence ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
The final report details achievements and slippages of a model demonstration center which served 46 preschool handicapped children. Documented are milestones in such areas as direct and supplementary services to children (identification, evaluation); parent/family participation (large and small group meetings, individual parent participation); development of a procedure to insure longitudinal program continuity, staff development for project and district personnel and volunteers); dissemination; and evaluation (child progress, cost effectiveness, parent involvement, replication outcomes). Among other achievements noted are increased coordination between community agencies. (CL)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: G007703070.
ERIC Note: Apendixes A-J containing forms and working papers omitted due to reproduction problems.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Demonstration Programs; Disabilities; Preschool Education; Program Descriptions; Program Effectiveness; Program Evaluation; Reports, Evaluative